The cGAS-STING Pathway: Novel Perspectives in Liver Diseases - Xu, Dongwei; Tian, Yizhu; Xia, Qiang; Ke, Bibo (Frontiers in Immunology, 2021)
Liver diseases represent a major global health burden accounting for approximately 2 million deaths per year worldwide. The liver functions as a primary immune organ that is largely enriched with various innate immune cells, including macrophages, dendritic cells, neutrophils, NK cells, and NKT cells. Activation of these cells orchestrates the innate immune response and initiates liver inflammation in response to the danger signal from pathogens or injured cells and tissues. The cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway is a crucial signaling cascade of the innate immune system activated by cytosol DNA. Recognizing DNA as an immune-stimulatory molecule is an evolutionarily preserved mechanism in initiating rapid innate immune responses against microbial pathogens. The cGAS is a cytosolic DNA sensor eliciting robust immunity via the production of cyclic GMP-AMPs that bind and activate STING. Although the cGAS-STING pathway has been previously considered to have essential roles in innate immunity and host defense, recent advances have extended the role of the cGAS-STING pathway to liver diseases. Emerging evidence indicates that overactivation of cGAS-STING may contribute to the development of liver disorders, implying that the cGAS-STING pathway is a promising therapeutic target. Here, we review and discuss the role of the cGAS-STING DNA-sensing signaling pathway in a variety of liver diseases, including viral hepatitis, nonalcoholic fatty liver disease (NAFLD), alcoholic liver disease (ALD), primary hepatocellular cancer (HCC), and hepatic ischemia-reperfusion injury (IRI), with highlights on currently available therapeutic options.